113k views
2 votes
Rewrite each expression as a polynomial in standard form: x^2-5x+6 ÷ x-3 + x^3-1 ÷ x-1

1 Answer

6 votes

Answer:

So in standard form equation will be
x^2+2x-1

Explanation:

We have given expression
(x^2-5x+6)/(x-3)+(x^3-1)/(x-1)

Let first we solve first part of the expression

So
(x^2-5x+6)/(x-3)=(x^2-3x-2x+6)/(x-3)=((x-3)(x-2))/(x-3)=x-2

Now second part
(x^3-1)/(x-1)

We know the algebraic identity
a^3-b^3=(a-b)(a^2+ab+b^2)

So by using this identity


(x^3-1)/(x-1)=((x-1)(x^2+x+1))/(x-1)=x^2+x+1

Now adding first and second part


x-2+x^2+x+1=x^2+2x-1

So in standard form equation will be
x^2+2x-1

User Wisnu Wijokangko
by
5.8k points